ANALISIS MODAL SOSIAL ARSYADJULIANDI RACHMAN PADA PEMILIHAN GUBERNUR RIAU DI KOTA PEKANBARU TAHUN 2018 - M. Fazri Waskita; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
In the 2018 Riau Governor election, social capital was one of the assets that might increase candidates' chances of being elected to office. According to Bourdeiu, social capital takes the shape of actual and future assets that a person owns from an established and ongoing social network that offers assistance to its members collectively. It is impossible to isolate social capital from an individual's habitus and the environment where capital is contested and maintained (field). However, it is asserted that Andi Rachman and Suyatno Pair lost the 2018 Riau Governor Election due to their failure to effectively utilize their social capital. This study intends to outline the types and applications of Arsyadjuliandi Rachman's social capital and how it affected the 2018 Riau Governor Election in Pekanbaru City. Using a descriptive qualitative methodology, this study. Location Purposive process techniques were used to carry out the research, which was done in the city of Pekanbaru. Interviews and documentation were used as data gathering methods, while qualitative descriptive analysis was used as a method of data analysis. The findings of this study demonstrate that Andi Rachman does possess significant amounts of several types of social capital. These include his physical appearance and personality, his family links and networks, his positions and accomplishments, and social organizations and groups. social. All of these forms of social capital can promote and get support from the community when used effectively by Andi Rachman. Andi Rachman failed to win the community's entire support and trust due to the negative effects of unpleasant issues on the party that took Andi Rachman's place to run for governor of Riau in 2018. As a result, he lost. Keywords: Social capital, a losing candidate, and a governor are elected